2022
DOI: 10.1007/s10461-022-03585-w
|View full text |Cite
|
Sign up to set email alerts
|

Utility and Impact of the Implementation of Same-Day, Self-administered Electronic Patient-Reported Outcomes Assessments in Routine HIV Care in two North American Clinics

Abstract: The PROgress study assessed the value and feasibility of implementing web-based patient-reported outcomes assessments (PROs) within routine HIV care at two North American outpatient clinics. People with HIV (PWH) completed PROs on a tablet computer in clinic before their routine care visit. Data collection included PROs from 1632 unique PWH, 596 chart reviews, 200 patient questionnaires, and 16 provider/staff questionnaires. During an initial setup phase involving 200 patients, PRO results were not delivered t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 37 publications
0
27
0
Order By: Relevance
“…Potential mechanisms were early responsiveness to symptoms preventing adverse downstream consequences and ability to tolerate chemotherapy longer than the usual care group. Short et al assessed the value and feasibility of web-based PRO assessments within routine HIV care (53). The study included 1630 HIV patients who completed PROs in the outpatient clinic before their routine care consultation.…”
Section: Examples Of Routine Use Of Prosmentioning
confidence: 99%
See 1 more Smart Citation
“…Potential mechanisms were early responsiveness to symptoms preventing adverse downstream consequences and ability to tolerate chemotherapy longer than the usual care group. Short et al assessed the value and feasibility of web-based PRO assessments within routine HIV care (53). The study included 1630 HIV patients who completed PROs in the outpatient clinic before their routine care consultation.…”
Section: Examples Of Routine Use Of Prosmentioning
confidence: 99%
“…Short et al. assessed the value and feasibility of web-based PRO assessments within routine HIV care ( 53 ). The study included 1630 HIV patients who completed PROs in the outpatient clinic before their routine care consultation.…”
Section: Examples Of Routine Use Of Prosmentioning
confidence: 99%
“…Detailed methodology has been previously described. 13 Eligible participants were aged ≥18 years with a diagnosis of HIV who attended a participating clinic for a routine visit during the study period and could sufficiently speak and understand English, Spanish, and/or Haitian Creole to be able to complete the PRO. Individuals with psychiatric, cognitive, or motor impairment and those visiting the clinic for a non-routine reason (ie, acute illness or injury) or to see a provider other than their primary HIV care provider were excluded.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…8 Screening assessments using patient-reported outcomes assessments (PROs) in routine HIV care can improve patient-provider communication and focus provider attention on symptoms or behaviors that may not otherwise be addressed, such as mental health issues and substance use. [9][10][11][12][13][14] Information obtained through PROs may also aid providers in identifying barriers to ART adherence among their patients. 15 For example, previous studies have demonstrated that substance use, depression, and dissatisfaction with ART are associated with suboptimal ART adherence among PWH who completed PROs at routine HIV clinic visits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation